The Production of Palm Kernel Shell Charcoal by the Continuous Kiln Method - Elham, Puad (2001)
The agro industry sector in Malaysia generates a significant amount of renewable biomass in the form of oil palm kernel residues. Palm kernel shells are one of the residues from oil palm industry and have long been used as fuel in boiler to produce steam and electricity for mill processes. These residues had disposal and environmental pollution problems. Carbonisation at present is a promising method to convert the palm kernel shells into charcoal. This study was carried out to determine the properties of palm kernel shell charcoal manufactured by the continuous kiln method. The carbonization of palm kernel shells was carried out in the 40 feet horizontal continuous kiln. The carbonization took placed at 400 DC, 500 DC and 600 DC, each for 30, 40, 50 and 60 minutes. The results show that the volatile matter 8.6% - 26.5%, low ash content 2.4% - 3.9% and high fixed carbon 70.7% - 88.2%. The bulk density of the charcoal is 661 -781 kg/m3. The palm kernel shell charcoal had reasonably high percentage of fixed carbon. The results indicate that palm kernel shell charcoal is suitable for industrial application such as a feedstock for the production of activated carbon.